Facile one-pot synthesis of aliphatic bridged diaryloxy compounds, cyclic and crown ethers under mild conditions - Sakate, Sachin; Kamble, Sumit; Chikate, Rajiv; Rode, Chandrashekhar (Supramolecular Chemistry, 2017)
We report here the facile, room temperature, catalyst free, one pot synthesis of aliphatic bridged diaryloxy compounds, cyclic and crown ethers. Anhydrous potassium carbonate (K2CO3) as a mild base along with dimethyl sulfoxide generates the phenoxide ion which facilitates the nucleophilic substitution of bromoalkanes to yield the corresponding crown ethers.